Electrospun fish skin gelatin scaffolds for functional tissue engineering of articular cartilage - Khoo, Weily (2021)
Articular cartilage is a soft tissue that covers bone joint surface. It has very low self-regenerative potential after injury, owing to its avascular nature. In recent years, hydrogels have been extensively studied as tissue engineering scaffolds for damaged articular cartilage. However, the use of fish skin gelatin as articular cartilage tissue engineering scaffold is remained unclear. Accordingly, the ultimate goal of this project is to investigate the feasibility of fish skin gelatin scaffold for articular cartilage tissue engineering application. Fish skin gelatin solution was first electrospun into fibrous scaffold under different solution feed rate (0.15 ml/h to 0.60 ml/h), applied voltage (9 kV to 18 kV) and spinning distance (10 cm to 25 cm). The scaffolds were visualized under SEM and mechanically tested in uniaxial tension and fracture mode I at displacement rate of 3 mm/min. Results revealed that scaffolds with fiber diameters ranged from 199 ± 15.75 nm to 795 ± 89.91 nm have been produced at different process parameters. After crosslinking with GA vapor, scaffolds were found to maintain their fibrous structure with improved aqueous stability and mechanical properties. The elastic modulus and fracture toughness of crosslinked scaffolds was found to achieve up to 363.50 ± 61.83 MPa and 8.81 ± 1.91 kJ/m2 respectively. The crosslinked electrospun scaffolds were stiffer and tougher than that of articular cartilage. Moreover, in vitro culture of human chondrocytes on scaffold revealed that fish skin gelatin scaffolds supported cell proliferation and attachment as well as ECM production. Besides that, in an attempt to mimic the layered structure and function of articular cartilage, graded electrospun scaffold was produced using sequential electrospinning process. Such scaffold presented gradually change in fiber diameter and packing density over the thickness. Overall, electrospun fish skin gelatin scaffolds produced in present work showed great promise for articular cartilage tissue engineering since they were mechanically stiff yet tough scaffolds which supported cell proliferation and GAGs accumulation.